Growth of morphology-controllable carbon nanocoils from Ni nanoparticle prepared by spray-coating method. (February 2015) - Ding, Er-Xiong; Geng, Hong-Zhang; Wang, Wen-Yi; Mao, Lihe; Wang, Yan; Zhang, Ze-Chen; Luo, Zhi-Jia; Wang, Jing; Yang, Hai-Jie; Pan, Lujun
Abstract: Morphology-controllable carbon nanocoils (CNCs) are synthesized by thermal chemical vapor deposition using Ni nanoparticle as catalyst prepared by spray-coating method. It is found that, with the increase of number of spray-coating times, the helicity of CNCs increases whereas the average line diameter and coil pitch decrease. Additionally, infrequent Y-junction CNCs and plait-like CNCs are found in the deposits. What is noteworthy is that, compared with dip-coating, spray-coating method can prepare more uniform catalyst on substrate, resulting in more CNCs with high purity.